Livestock in natural vegetative strips (NVS) and Gmelina cropping systems - Mamicpic, May Ann E.; Tinsley, Richard L.; Sununtar Setboonsarng; Lantican, Celso B.; Little, David C. (Bangkok : Asian Institute of Technology, 1997)
A survey of the natural vegetative strips (NVS) alley cropping and Gmelina arborea block planting adopters was conducted to characterize the livestock component of the systems. As the NVS farm area extends, the number of animals raised also increases to suppo1t draft power requirement. The number of livestock decreases with increasing Gmelina parcel size because bigger plantations belong to growers primarily involved in off-farm employment thus do not need draft animals. Natural vegetation is the major livestock feed supplemented by corn stover following the harvest season. The animals are tethered on grazing areas and under Gmelina stand but only after the trees reached 2 years. Manure application is not practiced due to limited labor. Inadequate milk production results from deficient diet and stress from fieldwork. One animal works an average total of 150 days per year, on and off farm. Hauling and transpo1t accounted for 42% of the total work. Based on a bioeconomic analysis using SCUAF linked to an economic spreadsheet, a hectare of NVS cropping can only supp01t 1.2 au recycling 22 kg N from manure. But the addition of animal to an NVS system resulted to higher economic returns through the draft and transp01t services and the gain in animal inventory. The animal production potential in a Gmelina plantation is relatively low supporting 0.6 au/ha. This however compensates for the negative returns during the early stages of tree growing. Improvement of the systems depends on the identification and integration of appropriate forage species.
A thesis submitted in pa11ial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1997
Keywords: Gmelina arborea; Livestock systems